Wspieranie empowermentu w sytuacji zinstytucjonalizowanego nauczania języków obcych: możliwości, wyzwania i ograniczenia - Blachowska-Szmigiel, Marzena (Neofilolog, 2017)
The aim of this article is to present opportunities, challenges and constraints related to the support of a student’s empowerment in the context of institutionalized foreign language teaching. In the first part of the article, we describe empowerment as the approach, the process and the action that support the growth of power in individuals, communities and organizations. In the following part we present teaching and learning of foreign languages as a process supporting student’s empowerment. In the last part, we point to a foreign language teacher as a source of opportunities, challenges and constraints related to the support of a student’s empowerment.